2017
DOI: 10.1037/vio0000099
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence against women in the European Union: The influence of male partners’ traditional gender roles and general violence.

Abstract: Objective: The influence of partners’ traditional gender role and partners’ level of general violence on intimate partner violence (IPV) against women has been studied separately most likely because they represent key aspects of apparently contrasting theoretical views. The main goal of the present study was to investigate the influence of both partners’ gender role and partners’ level of general violence on IPV against women. Method: Using data from 20,663 heterosexual women living with their partners from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 65 publications
(81 reference statements)
2
27
0
1
Order By: Relevance
“…The evidence available at this point in the literature is mixed. In the review of studies by Ørke et al (2018) , only one study reported a positive relationship between low income and victimization by multiple partners ( Vatnar and Bjørkly, 2008 ) while other research on IPV has informed of a negative relationship between satisfaction with income and both physical and psychological IPV ( Herrero et al, 2017b ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The evidence available at this point in the literature is mixed. In the review of studies by Ørke et al (2018) , only one study reported a positive relationship between low income and victimization by multiple partners ( Vatnar and Bjørkly, 2008 ) while other research on IPV has informed of a negative relationship between satisfaction with income and both physical and psychological IPV ( Herrero et al, 2017b ).…”
Section: Discussionmentioning
confidence: 99%
“…Interviewers were asked to assess whether each respondent’s responses were insincere overall: “Do you think the respondent was telling the truth in the interview?” Responses ranged from 1 ( yes, all the time ) to 4 ( not at all ; M = 1.19, SD = 0.46). Although other research with this same dataset has also controlled for privacy and safety during the interview ( Herrero et al, 2017b ), we did not include these variables in the analyses because of zero variance in some countries (Germany, Lithuania, Netherlands, Portugal, Sweden, and United Kingdom).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Carlson, 1984;Cummings, González-Guarda, & Sandoval, 2013;Han, Kim, & Tyson, 2010;Heise, 1998;Little & Kaufman, 2002;Tonsing, 2011). However, there have been some recent adoptions of the ecological framework to empirically analyze risk factors (e.g., Akhter & Wilson, 2016;Herrero et al, 2017). In the current research, we apply an empirical, ecological approach to provide more accurate information about the relevance of hostile sexism and attitudes toward IPV in predicting psychological aggression.…”
Section: An Ecological Approach To Investigating Ipvmentioning
confidence: 99%